Ingenious Malay wood carving as daylight filtering devices - Denan, Zuraini; Abdul Majid, Noor Hanita; Arifin, Norazah (Elsevier, 2015)
The carving of the traditional Malay house is not only aesthetical but also functional for filtering daylight. The carvings were commonly applied at the roof end as fascia boards, on the walls, on windows and other parts of opening design. The study focus on evaluating carving panels applied at the top of the traditional Malay house’s window. A computer simulation, the ECOTECT software, is conducted based on simplified carving ratio categories of solid and void (1:1- 1:99). The results will suggest the daylight levels filter through the carvings that can correlate with suitable task recommended by the guidelines.